2017
DOI: 10.1016/j.pgeola.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The stratigraphy and chronology of the fluvial sediments at Warsash, UK: implications for the Palaeolithic archaeology of the River Test

Abstract: This paper reports new fieldwork at Warsash which clarifies the terrace stratigraphic framework of the Palaeolithic archaeology of the region. Sections were recorded in former gravel pits and at coastal locations, supplemented by the use of ground penetrating radar and luminescence dating techniques. The region's extensive borehole archive was also analysed to produce a revised terrace stratigraphy at Warsash and for the Test valley as a whole. At Warsash, some of the sediments previously identified as the Mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…The data from the Dunbridge project demonstrate the considerable potential of watching-brief monitoring, coupled with funded analyses, of commercial quarry enterprises. Further light is shed on the timing on Levallois in the Solent region by detailed research in the Warsash area, one of the few sites in this region with good representation of Levallois technology (Hatch et al, 2017). In addition to confirming and OSL dating the suggested correlations in Harding et al (2012), this research suggested that the Levallois may have an even younger age, given its fresh condition and stratigraphical position at the surface of Terrace 3.…”
Section: Britainmentioning
confidence: 70%
“…The data from the Dunbridge project demonstrate the considerable potential of watching-brief monitoring, coupled with funded analyses, of commercial quarry enterprises. Further light is shed on the timing on Levallois in the Solent region by detailed research in the Warsash area, one of the few sites in this region with good representation of Levallois technology (Hatch et al, 2017). In addition to confirming and OSL dating the suggested correlations in Harding et al (2012), this research suggested that the Levallois may have an even younger age, given its fresh condition and stratigraphical position at the surface of Terrace 3.…”
Section: Britainmentioning
confidence: 70%
“…However, supporting evidence for structured landscape use comes from several sites where their location is on an older terrace, just above the floodplain. This is the case for the west London sites of Creffield Road and other locations in West Drayton and Yiewsley, and also Warsash at the Solent/Test confluence (Ashton et al ., ; Davis et al ., ; Hatch et al ., ). These positions would have provided good views across the valleys, but still in close proximity to a wide range of resources by the river and above the floodplain.…”
Section: Discussionmentioning
confidence: 97%
“…The identified pattern is based on the assumption that most, if not all, Levallois artefacts in Britain reflect Early Middle Palaeolithic, rather than Late Middle Palaeolithic, activity. As discussed above, this assumption is mainly based on good dating of all the major sites to between MIS 9 and 6, such as Ebbsfleet (Scott et al ., ), Crayford (Penkman et al ., ), Creffield Road (Scott, ), various locations in Yiewsley and West Drayton (Scott, ), Warsash (Davis et al ., ; Hatch et al ., ) and Pontnewydd Cave (Aldhouse‐Green et al ., ). Many other locations occur on the middle terraces of rivers (Wymer, ), or otherwise on poorly defined terraces on some of the lowland rivers, such as the Great Ouse or the Nene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both these examples, the interpretations have been based on the study of old collections, but in conjunction with a better understanding of their context. Much of the work of the Ancient Human Occupation of Britain project (Stringer 2005), the Solent River Palaeolithic Project (Davis 2013;Hatch 2014;Davis et al 2016;Hatch et al 2017) and, most recently, the Breckland Palaeolithic Project (Davis et al 2017) has concerned the stratigraphical, chronological and environmental contexts of old collections. In each case, a deeper understanding of the collection context has enabled old sites to be drawn into modern research and interpretation.…”
Section: Discussionmentioning
confidence: 99%